MG63 and MC3T3-E1 Osteoblastic Cell Lines Response to Raloxifene. (September 2013) - Muzio, L. Lo; Santarelli, A.; Orsini, G.; Memè, L.; Mattioli-Belmonte, M.; De Florio, I.; Gatto, R.; Gallusi, G.; Nocini, P.F.; Bertossi, D.; Emanuelli, M.; Putignano, A.; et al.
Bone resorption in edentulous regions often results in inadequate ridge for implant osseointegration. In order to overcome this problem, the use of osteoconductive biomaterials has been proposed as a carrier for different types of pharmacological molecules. Since raloxifene, a drug used in osteoporosis therapy, inhibits the osteoclast, but not osteoblast functions, it has been suggested to improve recovery during implant surgery. The present work evaluated in vitro the effect of raloxifene on two different cell populations: the human osteoblast-like cells (MG63) and osteoblasts derived from rat calvaria (MC3T3-E1). The morpho-functional investigations carried out showed a different behavior of the two cell lines. Raloxifene showed a stimulatory effect towards MG63 cell proliferation with a significant increase in cell viability after 7 days of culture. On the contrary, MC3T3-E1 cells showed a significant reduction in cell viability, when compared with the same cells at 72 h, or with the control cell population. The predominantly proliferative effect of raloxifene on MG63 cells is partly confirmed by the reduction of alkaline phosphatase activity, an early marker of osteoblast differentiation. The different effect of raloxifene on osteoblastic population in relationship to the type and age of the cell is an issue that needs further investigation.